Stress and Burnout among Medical Workers in Indonesia: A Study during COVID-19 Pandemic - Urfa Khairatun Hisan; Muhammad Miftahul Amri (Journal of Public Health Sciences, 2023)
The COVID-19 pandemic has infected at least half a billion people around the world. As frontline workers, medical professionals inevitably experienced significant workloads and pressure. Adding to the common causal of COVID-19 mental issues such as economic, fears, and anxiety, these factors make medical workers more vulnerable to stress and burnout. This manuscript aims to investigate stress and burnout levels among medical workers during the COVID-19 pandemic. In this study, we include medical workers in Indonesia (n=161). We used the coronavirus stress measure (CSM) and COVID-19 burnout scale (COVID-19-BS) to measure the variables of interest. The data is collected through an anonymous online survey from November 2021 to January 2022. The result shows that the majority of the participants experienced a high intensity of stress and mild burnout during the third wave of COVID-19 infection in Indonesia (June 2021-August 2021). In addition, the regression test shows that there is a significant relationship between stress and burnout caused by COVID-19. When the stress intensity increases, it is likely that the burnout risk also increases. Considering that medical workers play important roles in mitigating diseases such as the COVID-19 pandemic, the medical workers and healthcare stakeholders must pay attention to these factors in order to maintain the medical worker's mental health and healthcare service quality.